1975
DOI: 10.1063/1.88387
|View full text |Cite
|
Sign up to set email alerts
|

Hot-carrier instability in IGFET’s

Abstract: Injection of hot carriers from the channel region into the gate insulator of an IGFET imposes design constraints on the device dimensions and operating voltages. A fraction of the injected charge is trapped in the gate dielectric, and an undesirable shift in the operating characteristics results. The magnitude of the shift is related to the device dimensions, operating voltages, and gate dielectric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…With these experiments, Nicollian et al showed that there was a one-to-one correspondence between the hydrogen lost (i.e., reduced activity) and negative charge produced in a hydrated SiO layer in the presence of electron currents. Subsequently, other researchers observed threshold voltage instability and channel transconductance degradation in MOS transistors [33]- [35] where hot carriers were generated using the source-drain electric field.…”
Section: Degradation Of Transistors and Reliability Involving Hymentioning
confidence: 99%
“…With these experiments, Nicollian et al showed that there was a one-to-one correspondence between the hydrogen lost (i.e., reduced activity) and negative charge produced in a hydrated SiO layer in the presence of electron currents. Subsequently, other researchers observed threshold voltage instability and channel transconductance degradation in MOS transistors [33]- [35] where hot carriers were generated using the source-drain electric field.…”
Section: Degradation Of Transistors and Reliability Involving Hymentioning
confidence: 99%
“…During a strongly "on" condition with gate and drain voltages high, electrons flowing from source to drain can be scattered by the lattice and injected over the potential energy barrier at the oxide-silicon interface [4,36,37]. This problem will be present in all VLSI technologies as shorter channels are approached, although it will lessen with lower power supplies.…”
Section: % Stabilitymentioning
confidence: 95%
“…The barrier height between silicon and silicon dioxide is 3.1 eV. Equation 1 relates the electron temperature-(Te) and the silicon field, where k is the Boltzmann constant, A is the electron mean free path and c is the energy loss per optical phonon collision.…”
Section: Description Of the Phenomenonmentioning
confidence: 99%